Framework for the Implementation of the UN Guiding Principles on Business and Human Rights for the Protection of Women's Rights in Business Activities in Indonesia - Nurul Fatimah Khasbullah (Universitas Negeri Semarang, 2022)
The UN Guiding Principles on Business and Human Rights (UNGPs) is adopted as the first international instrument that provides answer to the long debate on whether or not a business has human rights responsibilities. Although the state and business have different responsibilities towards the fulfillment of human rights in business activities, the UNGPs emphasizes the urgency of a gender dimension for all stakeholders in implementing its principles. The purpose of this study is to describe the responsibilities of business actors in implementing the gender dimensions of the UNGPs and to examine its application in Indonesia. The research uses a normative juridical method with a descriptive analytical and statue approach. The result of the study shows that the adoption of the UNGPs has been carried out in Indonesia through the National Action Plan for Human Rights with women as one of the focus groups. However, the implementation has not comprehensively complied with the overall gender perspective in the UNGPs principles.